1994
DOI: 10.1111/j.1476-5381.1994.tb17143.x
|View full text |Cite
|
Sign up to set email alerts
|

The interaction of α‐human atrial natriuretic peptide (ANP) with salbutamol, sodium nitroprusside and isosorbide dinitrate in human bronchial smooth muscle

Abstract: 1 Contractions in human bronchial rings evoked by methacholine (10-6M) were reversed by single contractions of a-human atrial natriuretic peptide (10-6 M), salbutamol (10-6 M), sodium nitroprusside (10-6 M) or isosorbide dinitrate (4.2 x 10-M) and the extent of the relaxations compared. The activity of combinations of ANP with salbutamol, sodium nitroprusside and isosorbide dinitrate were compared with those for each agonist alone. 2 ANP and salbutamol were equipotent in reversing methacholine-evoked contracti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

1995
1995
2013
2013

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 28 publications
1
4
0
Order By: Relevance
“…In a previous study (Torphy et al, 1992), we demonstrated that PDE4 activity is up-regulated by salbutamol, used alone or in combination with rolipram, over a concentration range of 10 nM to 10 M. This range is identical to that required to relax human airway smooth muscle in vitro (Goldie et al 1986;Nally et al, 1994). While it is virtually impossible to determine the local concentrations of inhaled salbutamol within the airway, this information strongly suggests that salbutamol up-regulates PDE4 activity at clinically relevant concentrations.…”
Section: Effect Of Pde4 Up-regulation On Agonist-stimulated Ca 2ϩsupporting
confidence: 52%
“…In a previous study (Torphy et al, 1992), we demonstrated that PDE4 activity is up-regulated by salbutamol, used alone or in combination with rolipram, over a concentration range of 10 nM to 10 M. This range is identical to that required to relax human airway smooth muscle in vitro (Goldie et al 1986;Nally et al, 1994). While it is virtually impossible to determine the local concentrations of inhaled salbutamol within the airway, this information strongly suggests that salbutamol up-regulates PDE4 activity at clinically relevant concentrations.…”
Section: Effect Of Pde4 Up-regulation On Agonist-stimulated Ca 2ϩsupporting
confidence: 52%
“…ANP also relaxes human airways in vitro. ANP was reported to reverse and protect against methacholineinduced contraction of human bronchi (6,20,84). ANP was more potent than SNP and salbutamol (20).…”
Section: What Are the Biological Effects Of Particulate Gc Activatorsmentioning
confidence: 99%
“…Further studies addressing possible interactions in vitro may be of great interest. The demonstration of an additive effect of NO and NO donors on ␤ 2 -agonist-induced bronchodilation in asthmatic subjects (50,104) and that a combination of ANP and salbutamol evokes a greater effect than either alone in reversing and protecting against methacholine-evoked contraction in isolated human bronchi (84) suggest that such combinations could be of benefit in the treatment of asthma, allowing lower doses of each individual drug to be used.…”
Section: Cross Talk Between Cgmp and Camp Pathwaysmentioning
confidence: 99%
“…ASTHMA there is a theoretical advantage in the concomitant use of BNP together with ␤-agonist inhalation. 12 BNP increases cellular concentration of cyclic guanosine monophosphate (cGMP) secondary to a rise in intracellular Ca ϩϩ concentration. 13,14 This is in contrast to cyclic adenosine monophosphatedependent stimulation of the receptor on bronchial smooth-muscle cells receptors by ␤-agonists.…”
Section: Original Researchmentioning
confidence: 99%